The challenges of remote learning in public education networks (Research, Society and Development, 2022)
This article aims to reflect on the challenges of Remote Learning in Brazilian public schools during the COVID-19 pandemic. The general objective is to identify the main challenges faced by schools for the implementation of Remote Learning and the possibilities found for ensuring that its students had access to pedagogical activities and maintained their school bond. For this, we started a bibliographical research based on readings of studies already published on the subject and we carried out a search on news sites that bring reports about remote teaching. Through the study we can see that a large part of public school students still do not have access to remote teaching that takes place online through digital platforms and to carry out the activities they need to go to school to get the printed material. Through this study, we realize the need for support from the government to ensure digital inclusion and improve the infrastructure of schools, so that they can adapt to a new reality when presential return to classes is possible.